Behavioral Counseling Effectiveness Behavior Contract Technique to Decrease Behavior Academic Procrastination of Students - Purnama, Andre Septian; Mursidi, Agus; Trisnawati, Kartini Ayu (Universitas Malikussaleh, 2019)
In this study aims to: (1) determine the effectiveness of behavioral counseling behavior contract techniques in reducing the academic procrastination behavior of class XII IPS MAN 2 Banyuwangi students; (2) find out the differences between students of class XII IPS MAN 2 Banyuwangi between the experimental group and the control group that did not receive treatment. The design used is non-equivalent pretest-posttest control group. The sample of this study was 20 students of class XII IPS MAN 2 Banyuwangi which were divided into 2 groups. Academic procrastination behavior was measured using an academic procrastination behavior questionnaire. The data that has been obtained is then analyzed using descriptive analysis. The results showed that: (a) first, the tcount at the output showed the number 27,976 this meant a decrease. If t arithmetic> T table, then H0 is rejected. Which means 27,976> 1,833, thus because H0 is rejected, Ha is accepted, where Ha reads